Up-regulation of long non-coding RNA PANDAR is associated with poor prognosis and promotes tumorigenesis in bladder cancer. Issue 1 (December 2016) - Zhan, Yonghao; Lin, Junhao; Liu, Yuchen; Chen, Mingwei; Chen, Xiaoying; Zhuang, Chengle; Liu, Li; Xu, Wen; Chen, Zhicong; He, Anbang; Zhang, Qiaoxia; Sun, Xiaojuan; et al.
Abstract Background Long non-coding RNAs (lncRNAs) have emerged as biomarkers and important regulators of tumor development and progression. PANDAR (promoter of CDKN1A antisense DNA damage activated RNA) is a novel long non-coding RNA that acts as a potential biomarker and involves in development of multiple cancers. However, the clinical significance and molecular mechanism of PANDAR in bladder cancer is still unknown. In this study, we aimed to figure out the role of PANDAR in bladder cancer. Methods The relative expression level of lncRNA PANDAR was determined by Real-Time qPCR in a total of 55 patients with urothelial bladder cancer and in different bladder cancer cell lines. We inhibited PANDAR expression by transfecting PANDAR specific siRNA and enhanced PANDAR expression by transfecting a PANDAR expression vector (pcDNA3.1-PANDAR). Cell proliferation was determined by using both CCK-8 assay and Edu assay. Cell apoptosis was determined by using ELISA assay, Hoechst 33342 staining and Flow cytometry. Cell migration was determined by using transwell assay. All experimental data from three independent experiments were analyzed byχ 2 test or Student'st -test and results were expressed as mean ± standard deviation. Results We found that PANDAR was significantly up-regulated in bladder cancer tissues compared with paired-adjacent nontumorous tissues in a cohort of 55 bladder cancer patients. Moreover, increased PANDAR expression was positively correlated with higher histological grade (P < 0.05) and advanced TNM stage (P < 0.05). Further experiments demonstrated that inhibited cell proliferation/migration and induced apoptosis by silencing PANDAR were also observed in bladder cancer cells. Furthermore, over expression of PANDAR in bladder cancer cells promoted the proliferation/migration and suppressed apoptosis. Conclusions These findings demonstrate that PANDAR plays oncogenic roles in bladder cancer and PANDAR may serve as a potential prognostic biomarker and therapeutic target of bladder cancer.